A polgári kori pénzintézeti hálózat kialakulása a Délnyugat-Dunántúlon Baranya, Somogy, Tolna, Zala megyék. : THE DEVELOPMENT OF A FINANCIAL INSTITUTIONAL NETWORK DURING THE BOURGEOIS ERA - Halász, Imre (Közép-Európai Közlemények, 2020)
By this time the basis of the modern banking system developed after 1867 - banks, savings banks, co-ops (provident societies, mutual societies, etc. where the capital is not made up of shares rather business deposits) is a quarter of a century old. Its beginnings are considered to be the period before 1848. The second temporary period was the one and a half decade between 1850 and 1865 when during its earlier years neo-absolutist regulations considered financial institutions to be in the same category as profit-oriented societies. During this period, in the Sopron administrative region that incorporated most of Transdanubia, there were seven savings banks in operation in the following towns and cities: Sopron, Veszprém, Győr, Kőszeg, Nagykanizsa, Szekszárd, Pécs. Based on data from 1853, savings banks were ranked based on their capital and annual profit. Based on capital, Kőszeg ranked 2nd, Pécs 4th, Szekszárd 6th and Nagykanizsa 7th, while concerning profit Kőszeg came 1st, Pécs 3rd, Nagykanizsa 4th and Szekszárd 7th. The “bank founding rush” period that began in 1866 and intensified through the Compromise of 1867 up until 1873 resulted in 564 financial institutions in Hungary. In the above-mentioned regions, banks were established by the Austro-Hungarian Bank which extended its operations to almost every larger settlement through local banks and savings banks. True change however was only brought on by the establishment of local financial institutions. By 21st December 1874 after the crisis of 1873 there were 44 savings banks in operation and their total assets were measured at over 18,5 million Forints. The network of several savings banks and newly established credit unions resulted in continuously expanding crediting activities that contributed to the economic development of the region.